Development of Socio-Scientific Issues-Based Learning Modules to Train Students' Creative Thinking Skills in Nanotechnology for Grade X Senior High School/MA - Mimi Herman; Miftahul Jannah (Universitas Lampung, 2025)
This study aims to test the validity and practicality of socio-scientific issues-based learning modules to train students' thinking skills in nanotechnology. The method used in this study was Research and Development (R&D) using the 4-D development model. The test subjects were students in class X E4 at SMA Negeri 2 Batusangkar. The data analysis technique was a validity and practicality test of the respondent questionnaire. The results showed that the validity of the material in the learning module based on socio-scientific issues was 87% and the language validation was 81%. The results of the practicality test from the respondent questionnaire were 95% and the level of students' creative thinking was 84%. Based on the results of the study, it can be concluded that the learning module based on socio-scientific issues to train students' creative thinking skills is very valid and very practical to use.